2012
DOI: 10.1016/j.rbmo.2012.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Unexplained infertility: an update and review of practice

Abstract: Of the couples unable to conceive without any identifiable cause, 30% are defined as having unexplained infertility. Management depends on duration of infertility and age of female partner. This review describes and comments on the definition and evidence for the management of unexplained infertility. A literature search was conducted in EMBASE, Medline, Ovid and Cochrane Database of Systematic reviews using the terms 'infertility', 'unexplained infertility', 'idiopathic infertility', 'definition of infertilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
133
0
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(143 citation statements)
references
References 80 publications
4
133
0
6
Order By: Relevance
“…1 Infertility occurs in one out of five couple of reproductive age and in ten to twenty per cent of these cases, there seems to be no definitive cause, therefore these are classified as unexplained infertility. 2,3 Studies by Boivin et al found that the prevalence of infertility was nine per cent, for less developed countries. 4 In Britain male factor infection accounts for 25% of infertile couple while 25% remain unexplained and 50% are female cause with 25% being due to anovulation and 25% tubal problem/others.…”
Section: Introductionmentioning
confidence: 99%
“…1 Infertility occurs in one out of five couple of reproductive age and in ten to twenty per cent of these cases, there seems to be no definitive cause, therefore these are classified as unexplained infertility. 2,3 Studies by Boivin et al found that the prevalence of infertility was nine per cent, for less developed countries. 4 In Britain male factor infection accounts for 25% of infertile couple while 25% remain unexplained and 50% are female cause with 25% being due to anovulation and 25% tubal problem/others.…”
Section: Introductionmentioning
confidence: 99%
“…To date, there is no uniform definition for UI [6]. With the marvelous advancement in illumination and magnification, endoscopy would add a lot for the diagnostic work-up for cases with UI.…”
Section: Discussionmentioning
confidence: 99%
“…It is idiopathic in the sense that its cause remains unknown even after an infertility work-up, usually including semen analysis in the man and assessment of ovulation and fallopian tubes in the woman [6]. In Assiut, we believe that diagnostic laparoscopy is an integral step of the diagnostic work-up of any infertile couple before saying the term "unexplained".…”
Section: Introductionmentioning
confidence: 99%
“…The development of better methods of diagnosis due to better understanding of physiology of ovulation, advent of ultrasound, endoscopy and other modern equipments have changed the whole approach to this problem. [6]. Possible Etiologies for UI may include hostile cervical mucus [7], subtle ovulatory dysfunction [8], luteal-Phase Defect [9], impaired fertilizing ability of oocytes specially when associated with raised LH levels, hyperprolactinemia [10], sperm dysfunction and antisperm Antibodies (151endometrial Steroid receptor defects [12], some genetic [13], psychological [14] or immunological Causes [15].…”
Section: Dilemma Of Definition Of Unexplained Infertility (Ui)mentioning
confidence: 99%